GAMBARAN HISTOPATOLOGI AORTA TIKUS WISTAR YANG TERPAPAR ASAP ROKOK - Nazlyza, Lapatta (Universitas Sam Ratulangi, 2013)
Abstract: Cigarette smoking is one of the high risk factor of atherosclerosis. Atherosclerosis signed by plaque in artery and can caused constriction in the blood vessels. Atherosclerosis often occured in the blood vessels of the aortic. The purpose of these study is to see the histopatologic image of wistar rats aortic after being exposed by cigarrete smoke. This experimental study conducted throughout 5months using 10 rats wistar devided into 3 groups. Group A as a negative control (2 rats). Group B are exposed by cigarette smoke as much 24 cigarettes for 20 days (4 rats). Group C exposed by cigarette smoke as much 20 cigarette per day for 30 days (4 rats). The rats has been autopsied at the last 20 and 30 days and then continue made histology preparation with HE staining. The examination result shows by the microscopic image of the group A wistar rats aortic are normal. Group B showed a layer of foam cells in the tunica intima media. Group C showed foam cells in the intima and the media have started to protrude into the lumen. As a conclusion the wistar rats that are exposed by cigarrete smoke during 20 to 30 days showed a fatty streak (foam cell) on tunica intima and media aortic as early lesions in the process of atherosclerosis. Keywords: atherosclerosis, cigarette. Abstrak: Rokok merupakan salah satu faktor pencetus terjadinya aterosklerosis. Aterosklerosis ditandai oleh adanya plak di arteri yang dapat menyebabkan penyempitan pada pembuluh darah. Aterosklerosis sering terjadi pada pembuluh darah aorta. Tujuan penelitian ini untuk dapat melihat gambaran histopatologi aorta tikus wistar setelah dipapar dengan asap rokok. Penelitian eksperimental ini dilakukan selama 5 bulan dengan menggunakan 10 ekor tikus wistar yang dibagi dalam 3 kelompok. Kelompok A kontrol negatif (2 ekor). Kelompok B dipapari asap rokok sebanyak 24 batang perhari selama 20 hari (4 ekor). Kelompok C dipapari asap rokok sebanyak 24 batang perhari selama 30 hari (4ekor). Tikus diotopsi pada hari ke 20 dan 30 dan dibuat preparat histologi dengan pengecatan HE. Hasil pemeriksaan menunjukkan gambaran mikroskopik aorta tikus wistar kelompok A normal. Kelompok B menunjukkan adanya sel busa pada lapisan tunika intima, sampai tunika media. Kelompok C menunjukkan sel busa pada tunika intima sampai media dan sudah mulai menonjol ke lumen. Simpulan: tikus wistar yang dipapari asap rokok selama 20 sampai 30 hari menunjukkan adanya fatty streak (selbusa) pada tunika intima dan media aorta sebagai lesi awal dalam proses aterosklerosis. Kata Kunci: aterosklerosis, rokok.